2021
DOI: 10.7705/biomedica.5604
|View full text |Cite
|
Sign up to set email alerts
|

Definición diagnóstica en una familia con malattia leventinese en Colombia

Abstract: La malattia leventinese es una enfermedad hereditaria autosómica dominante, cuyos síntomas se inician entre la segunda y la cuarta décadas de la vida. Se caracteriza por la aparición de drusas localizadas entre el epitelio pigmentario de la retina y la membrana de Bruch; suele reducir la visión drásticamente y progresar a ceguera. La variante patogénica p.Arg345Trp en el gen EFEMP1 se ha asociado con esta enfermedad.Se presenta aquí la caracterización clínica y molecular de una familia con malattia leventinese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…Black circles plot proportions from the UK (present study), from an early large study of five families, 14 and from many cases pooled from many subsequent reports. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] The red diamond plots the proportion when all these cases are pooled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Black circles plot proportions from the UK (present study), from an early large study of five families, 14 and from many cases pooled from many subsequent reports. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] The red diamond plots the proportion when all these cases are pooled.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier paper 14 that pointed to the relevant chromosomal locus did show pedigrees for five families (92 affected individuals), from which numbers of affected males and females could be extracted (these were 40 and 52, respectively). Since then, several publications have reported additional cases [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] : these cases were reviewed (avoiding mutual overlap or overlap with the cohort in the current study); of 55 reported patients, 20 were males and 35 were females. The bottom of Figure 2 plots proportions with CIs.…”
Section: Pooling With Previously Published Best and Efemp1-associated...mentioning
confidence: 99%
“…It is characterized by the accumulation of macular and peripapillary yellow white deposits (drusen) between retinal pigment epithelium and bruchs membrane [3] . Visual acuity is preserved until central atrophy; pigment proliferation or choroidal neovascularization develops [4,5] . Genetic counselling and molecular diagnosis are recommended for these individuals to differentiate from age related macular degeneration [4,6] .…”
Section: Introductionmentioning
confidence: 99%